1998
DOI: 10.1016/s0378-1097(97)00534-x
|View full text |Cite
|
Sign up to set email alerts
|

Transient increases in colony counts observed in declining populations of Campylobacter jejuni held at low temperature

Abstract: Colony forming unit counts of Campylobacter jejuni were serially determined in a variety of microcosms in which growth was not expected. Unremitting decline in colony counts occurred in nutrient-free systems, however, transient increases were observed in human faecal emulsions and nutrient media on storage at between 1 and 25³C. The phenomenon, which was more pronounced at lower temperatures, could not be attributed to sampling errors, cell clumping or the influence of minor fluctuations in experimental condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Even though campylobacters are microaerophilic organisms, and thus sensitive to atmospheric oxygen, reports have shown that Campylobacter spp. have the ability to survive for prolonged periods in cold water, possibly being protected by biofilms (6,7). This could enhance C. jejuni survival in the environment during cooler periods of the year and thereby increase the exposure of birds to C. jejuni organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Even though campylobacters are microaerophilic organisms, and thus sensitive to atmospheric oxygen, reports have shown that Campylobacter spp. have the ability to survive for prolonged periods in cold water, possibly being protected by biofilms (6,7). This could enhance C. jejuni survival in the environment during cooler periods of the year and thereby increase the exposure of birds to C. jejuni organisms.…”
Section: Discussionmentioning
confidence: 99%